Skeletal Muscle Adaptations and Performance Outcomes Following a Step and Exponential Taper in Strength Athletes - Travis, S. Kyle; Zwetsloot, Kevin A.; Mujika, Iñigo; Stone, Michael H.; Bazyler, Caleb D. (Frontiers in Physiology, 2021)
Before major athletic events, a taper is often prescribed to facilitate recovery and enhance performance. However, it is unknown which taper model is most effective for peaking maximal strength and positively augmenting skeletal muscle. Thus, the purpose of this study was to compare performance outcomes and skeletal muscle adaptations following a step vs. an exponential taper in strength athletes. Sixteen powerlifters (24.0±4.0 years, 174.4±8.2 cm, 89.8±21.4 kg) participated in a 6-week training program aimed at peaking maximal strength on back squat (initial 1-repetition maximum [1RM]: 174.7±33.4 kg), bench press (118.5±29.9 kg), and deadlift (189.9±41.2 kg). Powerlifters were matched based on relative maximal strength, and randomly assigned to either a) 1-week overreach and 1-week step taper or b) 1-week overreach and 3-week exponential taper. Athletes were tested pre- and post-training on measures of body composition, jumping performance, isometric squat, and 1RM. Whole muscle size was assessed at the proximal, middle, and distal vastus lateralis using ultrasonography and microbiopsies at the middle vastus lateralis site. Muscle samples (n=15) were analyzed for fiber size, fiber type (MHC-I, -IIA, -IIX, hybrid -I/IIA) using whole muscle immunohistochemistry and single fiber dot blots, gene expression, and microRNA abundance. There were significant main time effects for 1RM squat (p<0.001), bench press (p<0.001), and deadlift, (p=0.024), powerlifting total (p<0.001), Wilks Score (p<0.001), squat jump peak-power scaled to body mass (p=0.001), body mass (p=0.005), fat mass (p=0.002), and fat mass index (p=0.002). There were significant main time effects for medial whole muscle cross-sectional area (p=0.006) and averaged sites (p<0.001). There was also a significant interaction for MHC-IIA fiber cross-sectional area (p=0.014) with post-hoc comparisons revealing increases following the step-taper only (p=0.002). There were significant main time effects for single-fiber MHC-I% (p=0.015) and MHC-IIA% (p=0.033), as well as for MyoD (p=0.002), MyoG (p=0.037), and miR-499a (p=0.033). Overall, increases in whole muscle cross-sectional area, fiber cross-sectional area, MHC-IIA fiber cross-sectional area, and MHC transitions appeared to favor the step taper group. An overreach followed by a step taper appears to produce a myocellular environment that enhances skeletal muscle adaptations, whereas an exponential taper may favor neuromuscular performance.